Strategies for maintaining the health of the musculoskeletal system from an occupational therapy approach aimed at administrative assistants who use video terminals at the mariana university (Cuidado y Ocupación Humana, 2024)
With the passage of time, the use of video terminals has become more common within companies to maximize the work, however, currently there is a high rate of occupational diseases and musculoskeletal problems caused by exposure to the risk of dysergonemics due to long periods of time in static form, therefore, this research was conducted through a documentary review and a field research where the overall objective was to develop innovative strategies for maintaining the health of the musculoskeletal system from an Occupational Therapy approach, the present investigation was carried out by means of a documentary review and a field investigation where the general objective was to develop novel strategies for the maintenance of the osteomuscular system health from an Occupational Therapy approach directed to the administrative assistants who use video terminals within the Mariana University, The methodology used was from a quantitative paradigm, with an analytical and descriptive empirical approach, conducting a survey of sociodemographic characteristics and the application of the musculoskeletal exploration protocol, where it was evidenced as a result an affection in workers in body segments such as lumbar area and shoulder, therefore a booklet was designed as a strategy, which contains a series of activities from Occupational Therapy focused on the promotion and maintenance of musculoskeletal health and finally as a conclusion, it highlights the importance of presenting a good health at the musculoskeletal level for the benefit of work performance and it is expected that the proposed activities contribute to the welfare of each worker and the company.
Keywords: Dysergonomic; Videoterminal; Lumbar Region; Shoulder; Work Station